Evaluasi Kesesuaian Lahan Tanaman Pangan dan Perkebunan di Desa Belimbing, Kecamatan Pupuan, Kabupaten Tabanan - Sidabutar, Febrin; Adi, I Gusti Putu Ratna; Mega, I Made (Nandur; Vol 1 No 1 (2021), 2021)
This study aims to determine the actual and potential land suitability, limiting factors, improvement efforts and the making of suitability maps as well as land use directions for several food crops and plantations. The plants evaluated include: rice, corn, sugar palm, coffee, salak and coconut. This research was carried out in Belimbing Village starting from January 2021 to March 2021. Based on the results of overlapping soil type maps, slope maps and land use maps, four homogeneous land units were obtained. The method used is a survey, analysis and classification of land suitability by matching the quality and characteristics of the land with the requirements for plant growth that are evaluated for suitability. The evaluation results show that the actual land suitability class for several food crops and plantations is S3 (marginally suitable) to N (not suitable). The limiting factors in the study area are: temperature, rainfall, dry months, humidity, N-total, P 2 O 5 , available K, slope and erosion hazard. Improvement of land suitability class is carried out with improvement efforts, namely the provision of organic matter, fertilization, making planting terraces according to contours and land cover except temperature, rainfall (especially for plantation crops), dry months and humidity because they are permanent limiting factors. Potential land suitability classes for several food crops and plantations evaluated are S1 (very suitable) to S3 (marginally suitable), with limiting factors of temperature, rainfall, slope and erosion hazard. Recommendations for land use in BLIVSw and BLVSw are corn and BLIVKb and BLVKb are sugar palm and coconut.